Comparison of the Characteristics of Learning Responsibility and Science Process Skills of Junior High School Students in the Material of Composing Different Particles - Harizon; Asrial; Haryanto; Dwi Agus Kurniawan; Riska Fitriani; Rahmat Perdana (Postgraduate, University of Mataram, 2023)
Learning science is one of the ways that education works to improve the quality of human resources by enhancing personality and abilities. In this study, researchers adopted a specific quantitative methodology. The research instrument used a student learning responsibility questionnaire with 25 statements and observation sheets of students' scientific inquiry skills with 18 statements ranging from very bad to very good. 237 junior high school students from state schools on the east coast grade 7 were used as research samples selected using purposive sampling technique. Data from the research sample can be evaluated after it has been gathered. Both descriptive and inferential statistics were used in the data analysis. The results showed that there was a significant relationship between learning responsibility and science process skills of junior high school students in suburban cities. There is a positive and unidirectional relationship between student responsibilities and students' science process skills in science subjects for junior high school students in suburban cities as indicated by the correlation between student learning responsibilities and science process skills, a correlation coefficient of 0.710 is obtained. Based on the results of the Follow-up Test, the average responsibility of the three junior high school students in suburban cities is significantly different from the significance value used, which is 0.05. The significance value obtained for the character of responsibility is 0.020 which is lower than the significance value used, which is 0.05. The researcher suggests that future scientists utilize research findings as a source of information to carry out additional research and close gaps in their knowledge.